Teachers’ perceptions and practices of reflective portfolio work in professional development of English language teachers. - Ishfaq, Sadia (Journal of Peace, Development and Communication, 2022)
Abstract The study aims to explore teachers’ beliefs and practices of reflective journal keeping in professional development practices of English language teachers. The study also seeks to discover reflective teaching practices of teachers that lead to their professional development. The research uses qualitative approach to study. The sampling population consists of ten English language teachers from two public sector schools at Pakistan. The constructivism paradigm is used and sampling size is determined via convenient sampling. The data collection instruments comprise of semi-structured interviews and reflective journals. The semi-structured interviews are transcribed for analysis and themes are generated manually. The document analysis of reflective journals is carried out. The quality criterion of research is determined by ensuring ‘trustworthiness’ of qualitative research. The results of study showed that there is ‘lack of awareness’ among teachers about reflective teaching practices and ‘dearth of skilled practitioners’. Although teachers at public sector schools possess a love of teaching profession and make us of students’ feedback as self-evaluation tool but there is teachers’ dissatisfaction such as lack of government support and dearth of professional development training that deter the execution of ground breaking teaching methodologies. The teachers at public sector schools are in a dire need of professional development. The reflective journal keeping proved beneficial for teachers to develop ‘enhanced pedagogical skills’, ‘awareness about students’ needs’ and break from monotonous teaching routines.